Transgender Language on Jalan Sisingamangaraja Medan Sociolinguistic Studies - Nurintan, Siti (Institute of Computer Science (IOCS), 2019)
This study describes the process of waria vocabulary formation and the meaning of waria vocabulary at Jalan Sisingamangaraja Medan. The theory in this research is Goeffrey Leecch's theory (stylistic meaning) and language symptom theory. This research is field research. The method in this research is the interview method, the type of data in this study uses qualitative methods, the data in this study are primary data using the listening method and continued with the listening proficiently technique. The analysis in this study used a different method and used a change technique (Sudariyanto, 1993: 37). The results of this study conclude that the waria language is a unique and creative language, the use of waria is used by waria to communicate with each other, their language is a special and secret language. The meaning contained in the waria vocabulary is the meaning that arises based on the use of language based on its geographic environment, dialect and origin, and has the same meaning in Indonesian, except that the pronunciation of the word is different. The process of forming the transgender language is due to the following language symptoms, the symptom of paragraphs of adding phonemes at the end of words, the system of including the location of phonemes, apocopy of removing phonemes at the end of words, and syncope of removing phonemes in the middle of words